Impact on the Shipping Industry in Ecuador as a Result of the Financial Crisis in 2008. - Burgos Ubilla, Daniela Verónica (2017)
The present thesis analyzes the effect of the global financial crisis of 2008 on the shipping industry in Ecuador. For its purpose, the impact of the financial crisis was represented by the fluctuationof Federal Funds rates and the fluctuation of the U.S dollar; and as shipping indicators FOB, CIF and tons of Ecuadorian non-oil exports and imports weretaken into consideration. A longitudinal design was carried out and a simple regression analysis tested the hypothesis. The results of the analysis found no relationship between the Fed Funds rates and non-oil exports and imports of Ecuador, but a significant relationship between dollar fluctuations and non-oil exports was detected. However, the relationship was not statistically significant with non-oil imports apparently due to the effect of safeguards in Ecuador during that period. The outputs seem to match with the research of John B. Taylor who affirmed that the real problem of the financial crisis was not liquidity but counterparty risk. The shipping industry is interpreted as an intermediary party in international trade. This is why it is assumed that somehow the industry in Ecuador was affected by the financial crisis of 2008. In addition, the Cobweb Theorem can describe the shipping financial system based on speculations of prices fluctuation, demand and capacity; and it is also used as a rational benchmarking model.